(untitled) (Texas Journal of Philology, Culture and History, 2023)
Today, it is very important for everyone to know foreign languages. The world becoming increasingly globalized and bilingual is becoming the need of the hour. Since we have set ourselves the goal of building a competitive country, from now, our graduates of schools, lyceums, colleges and universities must have a perfect knowledge of at least two foreign languages. As it is known, there are four basic skills that every learner should acquire. They are listening, reading, writing and speaking. In this article the most crucial skill, writing, how to teach writing effectively with some strategies in the classroom are going to be discussed. It is impossible to simply describe what a good lesson should consist of due to the many variables that impact learning and understanding, including the individuality of every group of students, there are certain strategies that are widely considered to be helpful. That is why, some of the strategies is going to be discussed in this article.